2016
DOI: 10.1186/s12906-016-1233-7
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen (+)-pinoresinol exerts antitumor activity in breast cancer cells with different oestrogen receptor statuses

Abstract: BackgroundConsumption of virgin olive oil (VOO) has been associated with a low breast cancer incidence. Pinoresinol is a phytoestrogen that is typically found in VOO. Considering the role of oestrogen in breast cancer development and progression, we investigated the potential antitumor activity of pinoresinol in breast cancer cells.MethodsTo address this question, we treated MDA-MB-231 (oestrogen receptor [ER] negative) and MCF7 (ER+) human breast tumour cells and MCF10A human mammary epithelial cells (ER-) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…More than half of all breast cancers over express ER and approximately 70% of them respond to anti-estrogen (for instance tamoxifen) therapy [1]. Drug resistance issues have brought about the search for and the development of various hormonal therapies designed to inhibit ER action, while research on the mechanisms underlying resistance has cast light on the cellular mechanisms besides ligand binding, which control ER function [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of all breast cancers over express ER and approximately 70% of them respond to anti-estrogen (for instance tamoxifen) therapy [1]. Drug resistance issues have brought about the search for and the development of various hormonal therapies designed to inhibit ER action, while research on the mechanisms underlying resistance has cast light on the cellular mechanisms besides ligand binding, which control ER function [23][24].…”
Section: Discussionmentioning
confidence: 99%
“…An important contribute to the polyphenolic fraction was also exerted by pinoresinol that was the second most abundant polyphenol in CO and was not detected by Deiana et al (2019). Pinoresinol has been recently addressed to potentially have antitumor activity in human breast cancer cells (López-Biedma et al, 2016), although it has recently been demonstrated that pinoresinol is responsible for decreasing vitamin D intestinal absorption in rats (Goncalves et al, 2018). Phenolic acids and alcohols were detected in low amounts, while a good content of the flavonoids luteolin and apigenin, which was comparable to that reported by Deiana et al (2019), was detected.…”
Section: Phenolic Compositionmentioning
confidence: 99%
“…All searches returned a combined total of 50 studies published within our selected time frame (5 y). After filtering for relevance, we identified a total of 34 articles reviewed below ( 41 74 ). Some studies that were published outside our selected time frame (>5 y) were identified in post-hoc searches and also reviewed to enhance the perspective and provide additional commentary.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies had demonstrated pinoresinol (100 μM) had anti-proliferative effects on MDA-MB-231 cells (70 ± 6% cell survival) but not MCF7 cells (96 ± 7% cell survival) ( 126 ). Recently, pinoresinol treatment was shown to have cytotoxic effects on MDA-MB-231 cells at concentrations ranging from 0.001–100 μM, whereas only low levels (0.001–0.01 μM) were cytotoxic to MCF7 cells ( 74 ). Interestingly, the cytotoxic effect of pinoresinol may be specific to tumorigenic cells.…”
Section: Olive Oil and Tnbc: Reviewmentioning
confidence: 99%